PERAN KOMUNIKASI PIMPINAN DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN: Universitas Negeri Semarang - Dwi Yunita, Ghina; Suci Oktafiana, Nabila; Nisa Febriantika, Aulia; Melani Risky Ayu Anggraini, Sri; Nabila Aflah, Abhinaya (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
Effective leadership communication is a vital element in creating a positive work environment to increase employee motivation in an organization. This research aims to describe the role of leadership communication in increasing employee motivation. The author uses the literature review method from several articles to identify leadership communication in building clear and transparent communication between superiors and subordinates. The results of the literature review show that effective leadership communication plays a major role in creating motivation and improving performance. With this understanding, organizations can formulate appropriate communication strategies to create a productive and collaborative work environment to achieve common goals.